2016
DOI: 10.1155/2016/1451676
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Receptor Interacting Protein Kinases Attenuates Cardiomyocyte Hypertrophy Induced by Palmitic Acid

Abstract: Palmitic acid (PA) is known to cause cardiomyocyte dysfunction. Cardiac hypertrophy is one of the important pathological features of PA-induced lipotoxicity, but the mechanism by which PA induces cardiomyocyte hypertrophy is still unclear. Therefore, our study was to test whether necroptosis, a receptor interacting protein kinase 1 and 3 (RIPK1 and RIPK3-) dependent programmed necrosis, was involved in the PA-induced cardiomyocyte hypertrophy. We used the PA-treated primary neonatal rat cardiac myocytes (NCMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 43 publications
2
29
0
1
Order By: Relevance
“…11,12 Likewise, recent cardiovascular researches concerning RIPK1 primarily focus on its role in induction of necroptosis in ischemia/reperfusion(I/R) injury and heart failure, [13][14][15] and only a few studies point out that RIPK1 is involved in the TGF-b-induced activation of cardiac fibroblasts. 36 In our previous study, we found that RIPK1 mediates the palmitic acid (PA)-induced cardiomyocyte hypertrophy, and inhibition of RIPK1 by Nec-1 attenuates cardiomyocyte hypertrophy induced by PA. 18 Indeed, in the present study, we found that RIPK1 is important for hypertrophic growth of cardiomyocytes undergoing ERS induced by hypertrophic stimuli (pressure overload/AngII/ISO). Nonetheless, we further found that RIPK1 acts as a scaffold protein to activate NF-kB signaling in a kinase-independent mode.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…11,12 Likewise, recent cardiovascular researches concerning RIPK1 primarily focus on its role in induction of necroptosis in ischemia/reperfusion(I/R) injury and heart failure, [13][14][15] and only a few studies point out that RIPK1 is involved in the TGF-b-induced activation of cardiac fibroblasts. 36 In our previous study, we found that RIPK1 mediates the palmitic acid (PA)-induced cardiomyocyte hypertrophy, and inhibition of RIPK1 by Nec-1 attenuates cardiomyocyte hypertrophy induced by PA. 18 Indeed, in the present study, we found that RIPK1 is important for hypertrophic growth of cardiomyocytes undergoing ERS induced by hypertrophic stimuli (pressure overload/AngII/ISO). Nonetheless, we further found that RIPK1 acts as a scaffold protein to activate NF-kB signaling in a kinase-independent mode.…”
Section: Discussionsupporting
confidence: 53%
“…16,17 Moreover, our previous work has demonstrated that RIPK1 plays an important role in palmitic acid-induced cardiomyocyte hypertrophy. 18 Therefore, these facts raise an intriguing possibility that Xbp1s/RIPK1 may act as a novel signaling pathway in the development of cardiac hypertrophy. On the other hand, ROS-dependent modification of certain key signaling pathways is involved in the pathogenesis of cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, pharmacological inhibition of RIPK1 activity by necrostatin‐1 prevented necroptosis and ameliorated I/R injury in mice and rats (Anbin et al ., ). Inhibition of RIPK1 and RIPK3 also prevents cardiomyocyte necroptosis‐mediated cell death in response to hypertrophy‐induced lipotoxicity stress (Zhao et al ., ). Thus, understanding the pathological role of necroptosis sheds light on a new strategy to treat heart disease; however, the molecular mechanisms underlying necroptosis in the pathogenesis of heart diseases are needed to be fully delineated.…”
Section: Mechanisms Of Mitochondria‐mediated Cell Death In Cardiac DImentioning
confidence: 97%
“…Nec-1 has been used as evidence of the role of necroptosis in different disorders ( 8 , 23 , 24 ). Nec-1 exhibits protective effects against Parkinson's disease, cerebral ischemia injury, cardiomyocyte hypertrophy, Alzheimer's disease, stroke, and amyotrophic lateral sclerosis, in which oxidative stress or free radical injury is considered a potent inducer ( 23 25 ). However, the effect of Nec-1 on hypoxia-induced muscle wasting remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%